Determination of Caffeine and some other Drugs in Cappuccino, Nescafe, Cacao, Coffee samples collected from some Libyan Markets using High Performance Liquid Chromatography (RP-HPLC) - Elmanfe , Galal M.; Khalifa , Hana O.; Khreit , Osama; Abduljalil , Omukalthum (Journal of Pure & Applied Sciences, 2021)
This study aims to determine the caffeine and detection of some other drugs (which has commonly spread and caused suicides in the recent years in El-Bieda city - Libya) in cappuccino, nescafe, cacao and coffee samples using Reversed Phase - High Performance Liquid Chromatography (RP-HPLC). In the presented study, seventeen samples were collected from some Libyan markets. A rapid, simple and reliable extraction method is developed and validated for the determination of caffeine and other drugs in the samples under study using dichloromethan, n-hexane and methanol as the extracting solvents. The method is validated over a wide linear range of 2 – 10 µg/ml with correlation coefficients being consistently greater than 0.999. The minimum caffeine level was observed in the Nesquik (Cacao), Nestle Italiana S.P.A sample (2.9129 µg/ml), while the Nestla (Nescafe), Asbania sample showed the highest caffeine content (598.5315 µg/ml). The RP-HPLC measurements indicate that the results of caffeine concentrations in samples under study are in the range of 2.9129 - 598.5315 µg/ml with an average of 221.8630 µg/ml. The measurements by HPLC methods indicate that the samples under study are free from other drugs: (olanzapine, diazepam and alprazolam). The caffeine content in all the samples analyzed in this study are within the allowable limits set by the US Food and Drugs Administration and documented values.